Palladium-Catalyzed Chelation-Assisted C–H Bond Halogenation: Selective Chlorination of 2-Arylpyridines with Acid Chlorides - Jafarpour, Farnaz; Hazrati, Hamideh; Zarei, Samaneh; Izadidana, Sara (Synthesis, 2014)
Palladium-catalyzed chelation-assisted C–H bond halogenation of arenes using acid chlorides as chlorinating agents is reported. This method provides a monoselective, straightforward, and clean route for the construction of aryl chlorides as privileged motifs in organic transformations.
Keywords: aroyl chlorides; C–H activation; chlorination; palladium; 2-phenylpyridine